FAKTOR DAN STRATEGI PENCEGAHAN PEMARJINALAN BAHASA SUWAWA DI PROVINSI GORONTALO - Umar, Fatmah AR (LITERA, 2017)
Abstract The Suwawa language is the oldest local language or "tiyombu"used by the Suwawa ethnic community in the areas of Suwawa and Bone Pantai in Gorontalo Province since the ancient time (around 300 BC). The Suwawa language, both historically and juridically, has a very important position and function. However, this language has begun to be marginalized. This study aims to describe factors and strategies to prevent the marginalization of the Suwawa language in Gorontalo Province. The study used the qualitative descriptive approach. The data were collected through participant observations, in-depth interviews, and documentation. The results of the study are as follows. First, the marginalization of the Suwawa language of Suwawa is caused by: (1) conceptual, (2) operational, (3) attitudinal, and (4) language-attitudinal factors. Second, strategies to prevent the marginalization of the Suwawa languagecan be applied through: (1) education, (2) research and scientific activities, and (3) community service. Keywords: factors, strategies, prevention, marginalization, Suwawa language